Effect of Transplanting Date on Growth and Yield of Advanced Lines of Transplanted Aman Rice - Sultana, Amena; Shaikh, Nilufar Yasmin; Zahan, Mst Selima; Badshah, Md Adil; Akter, Romana; Issak, Mohammad (Research in Agriculture Livestock and Fisheries, 2020)
This research was conducted in order to investigate the effects of time of planting on the grain yield and yield components of three advanced lines of rice under the Agro Ecological Zone (AEZ), Modhupur Tract. The research was conducted as a split plot using Randomized Complete Block Design (RCBD) with three replications in the Aman season of 2016 under the research field of Bangladesh Rice Research Institute (BRRI), Gazipur. In this research, the dates 01 August, 16 August, 31 August and 16 September were considered as the main factor in the main plots, and the advanced lines/varieties BR(Bio)9786-BC2-119-1-1, BR(Bio)9786- BC2-132-1-3 and BRRI dhan49 (check variety) were regarded as the secondary factors in the sub plots. The results showed that planting time significantly affected the plant height, the number of panicle per meter square, the number of tillers per meter square, the number of grains per panicle, 1000-grain weight and grain yield. Among the cultivars, the advanced line BR(Bio)9786-BC2-119-1-1 and BR(Bio)9786-BC2-132-1-3 produced significantly higher plant height, the number of panicle, the number of tillers, the number of grains per panicle, 1000- grain weight and grain yield than check variety BRRI dhan49 in all transplanting dates. The advanced line BR(Bio)9786-BC2-119-1-1 and BR(Bio)9786-BC2-132-1-3 produced average 1.02 and 0.57 t ha-1 higher yields respectively over the check variety BRRI dhan49 under the transplanting date 01 August to 31 August. The highest growth duration (130-146 days) was observed for the check variety BRRI dhan49 that followed by BR(Bio)9786-BC2-132-1-3 (132- 141 days) and BR(Bio)9786-BC2-119-1-1 (130-140 days) Res. Agric., Livest. Fish.7(1): 01-07, April 2020